"Difficult patients" in the advanced stages of cancer as experienced by nursing staff: A descriptive qualitative study. (June 2020) - Dobrina, Raffaella; Chialchia, Sara; Palese, Alvisa
Abstract: Purposes: "Difficult patients", as labelled by staff members, have been studied for their peculiarities in primary care, family and internal medicine, physiotherapy, psychiatry, dermatology, and dentistry. However, no data has been documented on "difficult patients" in hospice care settings. The aim of the study was to address the following research questions: (a) When do nursing staff label a patient suffering from advanced cancer as "difficult" in a hospice care setting? (b) What are the problems that the nursing staff face in dealing with them, and (c) What are the specific strategies that nursing staff adopt in their daily practice to overcome issues and improve their relationship with "difficult patients"? Methods: A qualitative descriptive study design was performed in 2018 and reported according to the COnsolidated criteria for REporting Qualitative research. Three focus groups were conducted in three hospice settings in Northern Italy by involving 10 nurses and six nurses' aides. Three trained researchers performed interviews based on a set of open questions. Qualitative content analysis of the data collected was then performed by the same researchers. Results: Participants were labelled "difficult patients" according to three main themes: (1) "Feeling rejected"; (2) "Feeling uncomfortable with the life story experienced by the patient" and (3) "Experiencing the limits of the profession". Participants reported feeling "Frustrated", "Exhausted", "Powerless", "Overwhelmed" or "Embarrassed" when dealing with "difficult patients". Strategies to overcome these issues emerged. Conclusions: As in other settings, hospice care nursing staff perceive some patients as "difficult". However, differently from other contexts, "difficult patients" are perceived as such also due to their relatives, who are perceived, in some cases, as being even more "difficult" than the patients themselves. Nursing staff should be aware of their personal attitudes and emotions in caring for patients perceived as "difficult" in order to identify and timely apply strategies to overcome issues that may compromise the therapeutic relationship and quality of care. Highlights: As in other settings, hospice care nurses perceive some patients and family members as "difficult". Nurses experience frustration, powerlessness and embarrassment when dealing with perceived "difficult" patients and families. Identified strategies to overcome barriers in caring for perceived "difficult" families are education in communication skills on end-of-life decision-making, and on different end-of-life trajectories including a positive reframing of emotional challenges. Education and support are needed for hospice nursing team to deal with moral distress when facing patients suffering with refractory symptoms, when patients are refusing treatments, when there are family conflicts and when the intimacy line is being crossed.